Gas industry reform and the evolution of a competitive gas market in Malaysia - Maggie Kumar; Jonathan P. Stern (The Oxford Institute for Energy Studies, 2020)
Gas market liberalisation is at an early stage in Malaysia. Not all of the legal and regulatory framework for third-party access (TPA) was in place at the end of 2019, and there had been no new entrants. Using stakeholder analysis, this paper analyses obstacles to the development of a liberalised and competitive gas market, specifically the existence of long-term sales contracts for large sections of the market which is dominated by incumbents, and a lack of transparent and market-related prices which hinders market entry. The lack of progress during the 2019 TPA pilot phase, highlighted these obstacles and raised questions about how quickly liberalisation could develop in future, and whether additional structural and regulatory measures would be needed. The paper also examines whether the development of global and regional (ASEAN) LNG trading could facilitate competition in the domestic gas market.
Keywords: 330; Country and Regional Studies; Energy Policy; Gas; Gas Programme